Chemical Composition, Gastroprotective, and Antioxidant Activities of Schrebera arborea Fruits. Issue 1 (2nd January 2020) - Sofidiya, Margaret Oluwatoyin; Bamigbade, Olaoluwa; Basheeru, Kazeem; Adegoke, Olufunmilayo; Agunbiade, Foluso O.
ABSTRACT: The chemical composition, gastroprotective, and antioxidant activities of Schrebera arborea fruits were investigated. The solvent extracts were analyzed for fatty acid and polyphenolic content using gas chromatography-mass spectrometry (GC–MS) and high performance liquid chromatography (HPLC), respectively. Acute toxicity study was done by oral administration at 2, 000 mg kg –1 . Gastroprotective effect was evaluated at 50, 100, or 150 mg kg –1 in ethanol and indomethacin-induced ulcer models in rats. The antioxidant activities of the extract were also evaluated. Sitosterol (41.55%) was the major component identified by GC–MS. Quantitative HPLC analysis for phenolic compounds indicated the presence of gallic acid (0.19 mg g –1 ), caffeic acid (0.13 mg g –1 ), rutin (0.30 mg g –1 ), apigenin-7-glucoside (1.21 mg g –1 ), catechin (1.84 mg g –1 ), and kaempferol (6.53 mg g –1 ), respectively. The ethanolic extract of the fruit produced 63.5% and 80.8% inhibition of ethanol and indomethacin-induced ulcer at 100 mg kg –1, respectively. The extract at 100 mg kg –1 reduced MDA level and increased glutathione, catalase, and superoxide dismutase activities in rat stomach tissue. Significant radical scavenging antioxidant activity was recorded in vitro .